Coarse-scale vertical distribution of pelagic amphipods in two contrasting seasons of the southern Gulf of Mexico - Violante-Huerta, Marco; Sanvicente-Añorve, Laura; Alatorre-Mendieta, Miguel; Guerra-Castro, Edlin (Frontiers in Marine Science, 2025)
In the oceans, ecological analyses of pelagic amphipods have mainly focused on the epipelagic zone with few studies in the deep waters. In this study, a coarse-scale vertical analysis, between 0 and 1000 m depth, was performed in the southern Gulf of Mexico during summer and winter. We hypothesize greater differences between the epi-and mesopelagic zones during the summer, because of a stronger vertical gradient in environmental conditions, especially temperature. As well, we think that the zooplankton biomass (as a measure of food availability) will play a significant role in regulating the amphipod distribution and abundance. Zooplankton samples were obtained at five levels (0-200, 200-400, 400-600, 600-800, 800-1000 m) of the water column using a stratified net system during the winter of 2013 and summer of 2014 in the southern Gulf of Mexico. To probe vertical differences, the amphipod community was analyzed considering two assemblages defined a priori, the ‘epipelagic’ and the ‘mesopelagic’; and considering each of the five sampling levels as separate groups. Results indicated that assemblages were significantly different in both seasons (ANOSIM test, p < 0.05), but differences were stronger in winter, which contradicts the first hypothesis. The vertical hydrological structure during the summer was characterized by a deepening of 15-18°C temperature values towards the upper mesopelagic zone, resulting in less heterogeneity between the epi- and the mesopelagic zones. A BEST-BIOENV test was used to evaluate the degree of association between the environmental (temperature, salinity, zooplankton biomass) and biological (amphipod composition and density) matrices. As expected, the zooplankton biomass was the most important factor affecting the distribution of the amphipods, especially during the summer (rho = 0.319, p = 0.001). The dominant species was Lestrigonus bengalensis in winter and the juveniles of the genus Primno in summer. The SIMPER analysis also showed these taxa as responsible for the discrimination of the epi- and mesopelagic assemblages. In a finer analysis taking the sampling levels as a factor, results indicated that, during the summer, the 200-400 m level showed a differentiation from the other deep levels; again, the effect of the deepening of temperature values between 15 and 18°C, could be the responsible. Comparisons of day/night sampling time in the average amphipod abundance indicated that only the members of the infraorder Physosomata showed significant differences during the summer (ANOSIM test, p < 0.05), which could be indicative of a migratory process. The diversity of the assemblages in both seasons was analyzed using alpha diversity species accumulation curves and a completeness analysis, using the sampling coverage. Seasonally, the summer was more diverse, while in the vertical plane, the mesopelagic zone was more diverse than the epipelagic one. We suggest further studies in the poorly sampled mesopelagic zone of the ocean to better understand the ecology of the deep-sea pelagic amphipods.